Protein-inspired antibiotics active against vancomycin- and daptomycin-resistant bacteria - Mark A. T. Blaskovich; Karl A. Hansford; Yujing Gong; Mark S. Butler; Craig Muldoon; Johnny X. Huang; Soumya Ramu; Alberto B. Silva; Mu Cheng; Angela M. Kavanagh; Zyta Ziora; Rajaratnam Premraj; et al. (Nature Communications, 2018)
The antibiotic vancomycin inhibits bacterial cell wall synthesis by binding to a membrane-associated precursor. Here, Blaskovich et al. synthesize vancomycin derivatives containing lipophilic peptide moieties that enhance membrane affinity and in vivo activities against glycopeptide-resistant strains.